1988
DOI: 10.1017/s0950268800029459
|View full text |Cite
|
Sign up to set email alerts
|

Rubella-specific IgG subclass avidity ELISA and its role in the differentiation between primary rubella and rubella reinfection

Abstract: SUMMARYAn antiglobulin enzyme-linked immunosorbent assay for rubella-specific IgG1 and IgG3 was adapted to measure antibody avidity by incorporating a mild protein denaturant, diethylamine (DEA), into the serum diluent. Sera were tested at varying dilutions, both with and without DEA, if they contained sufficient specific IgG, or IgG3. The optical density (OD) was measured and curves were plotted. The highest OD (V) was noted and halved (V/2). The distance between the OD curves at V/2 was measured as the DEA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 13 publications
(17 reference statements)
2
47
0
1
Order By: Relevance
“…Overall, for this group of sera the mean Al was 60 % for DEA and 55 % for urea. DISCUSSION A number of reports have shown the value of measuring the avidity of specific antibody as a marker for recent primary infection [3,4,15]. These have generally considered the avidity of specific IgG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, for this group of sera the mean Al was 60 % for DEA and 55 % for urea. DISCUSSION A number of reports have shown the value of measuring the avidity of specific antibody as a marker for recent primary infection [3,4,15]. These have generally considered the avidity of specific IgG.…”
Section: Resultsmentioning
confidence: 99%
“…Assays which detect specific IgG subclasses [2] only occasionally help but determination of specific IgG avidity has proved of great value [3,4]. It has been shown that for the month after onset of the rash, rubella-specific IgG is of low avidity compared with specific IgG of longer duration and hence found in reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Relative avidity studies are useful for the differentiation between cases of primary and past infection or reinfection/reactivation in several viral infections [13,14,16,17,19,26,28], and it was hoped that they might provide a means of identifying cases of recent HIV infection. We therefore examined the relative avidity of anti-gp41, anti-p24 and anti-p17 antibodies in sequential and cross-sectional sera from cases of well-defined recent HIV seroconversion and of anti-gp41 and anti-p24 antibodies in sera from cases who have been HIV for longer than a year.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-gp41 avidity studies were carried out using an ELISA technique which expresses the avidity of antibodies under examination relative to the avidity of antibodies from cases of long-term immunity [16,17,19]. Behring Anti-HIV-1/-HIV-2 kits were adapted.…”
Section: Remote Casesmentioning
confidence: 99%
See 1 more Smart Citation